Anticoagulant reversal, blood pressure levels, and anticoagulant resumption in patients with anticoagulation-related intracerebral hemorrhage - Kuramatsu, Joji; Gerner, Stefan; Schellinger, Peter D.; Glahn, Joerg; Endres, Matthias; Sobesky, Jan; Flechsenhar, Julia; Neugebauer, Hermann; Juettler, Eric; Grau, Armin; Palm, Frederick; Roether, Joachim; et al. (Journal of the American Medical Association, 2015)
Although use of oral anticoagulants (OACs) is increasing, there is a substantial lack of data on how to treat OAC-associated intracerebral hemorrhage (ICH).To assess the association of anticoagulation reversal and blood pressure (BP) with hematoma enlargement and the effects of OAC resumption.Retrospective cohort study at 19 German tertiary care centers (2006-2012) including 1176 individuals for analysis of long-term functional outcome, 853 for analysis of hematoma enlargement, and 719 for analysis of OAC resumption.Reversal of anticoagulation during acute phase, systolic BP at 4 hours, and reinitiation of OAC for long-term treatment.Frequency of hematoma enlargement in relation to international normalized ratio (INR) and BP. Incidence analysis of ischemic and hemorrhagic events with or without OAC resumption. Factors associated with favorable (modified Rankin Scale score, 0-3) vs unfavorable functional outcome.Hemorrhage enlargement occurred in 307 of 853 patients (36.0%). Reduced rates of hematoma enlargement were associated with reversal of INR levels <1.3 within 4 hours after admission (43/217 [19.8%]) vs INR of >=1.3 (264/636 [41.5%]; P < .001) and systolic BP <160 mm Hg at 4 hours (167/504 [33.1%]) vs >=160 mm Hg (98/187 [52.4%]; P < .001). The combination of INR reversal <1.3 within 4 hours and systolic BP of <160 mm Hg at 4 hours was associated with lower rates of hematoma enlargement (35/193 [18.1%] vs 220/498 [44.2%] not achieving these values; OR, 0.28; 95% CI, 0.19-0.42; P < .001) and lower rates of in-hospital mortality (26/193 [13.5%] vs 103/498 [20.7%]; OR, 0.60; 95% CI, 0.37-0.95; P = .03). OAC was resumed in 172 of 719 survivors (23.9%). OAC resumption showed fewer ischemic complications (OAC: 9/172 [5.2%] vs no OAC: 82/547 [15.0%]; P < .001) and not significantly different hemorrhagic complications (OAC: 14/172 [8.1%] vs no OAC: 36/547 [6.6%]; P = .48). Propensity-matched survival analysis in patients with atrial fibrillation who restarted OAC showed a decreased HR of 0.258 (95% CI, 0.125-0.534; P < .001) for long-term mortality. Functional long-term outcome was unfavorable in 786 of 1083 patients (72.6%).Among patients with OAC-associated ICH, reversal of INR <1.3 within 4 hours and systolic BP <160 mm Hg at 4 hours were associated with lower rates of hematoma enlargement, and resumption of OAC therapy was associated with lower risk of ischemic events. These findings require replication and assessment in prospective studies.clinicaltrials.gov Identifier: NCT01829581.
EVALuna2:22354

Baseline magnetic resonance imaging of the optic nerve provides limited predictive information on short-term recovery after acute optic neuritis - Berg, Sebastian; Kaschka, Iris; Utz, Kathrin S.; Huhn, Konstantin; Laemmer, Alexandra; Lämmer, Robert; Waschbisch, Anne; Kloska, Stephan; Lee, De-Hyung; Dörfler, Arnd; Linker, Ralf (PLoS ONE, 2015)
In acute optic neuritis, magnetic resonance imaging (MRI) may help to confirm the diagnosis as well as to exclude alternative diagnoses. Yet, little is known on the value of optic nerve imaging for predicting clinical symptoms or therapeutic outcome.To evaluate the benefit of optic nerve MRI for predicting response to appropriate therapy and recovery of visual acuity.Clinical data as well as visual evoked potentials (VEP) and MRI results of 104 patients, who were treated at the Department of Neurology with clinically definite optic neuritis between December 2010 and September 2012 were retrospectively reviewed including a follow up within 14 days.Both length of the Gd enhancing lesion (r = -0.38; p = 0.001) and the T2 lesion (r = -0.25; p = 0.03) of the optic nerve in acute optic neuritis showed a medium correlation with visual acuity after treatment. Although visual acuity pre-treatment was little but nonsignificantly lower if Gd enhancement of the optic nerve was detected via orbital MRI, improvement of visual acuity after adequate therapy was significantly better (0.40 vs. 0.24; p = 0.04). Intraorbitally located Gd enhancing lesions were associated with worse visual improvement compared to canalicular, intracranial and chiasmal lesions (0.35 vs. 0.54; p = 0.02).Orbital MRI is a broadly available, valuable tool for predicting the improvement of visual function. While the accurate individual prediction of long-term outcomes after appropriate therapy still remains difficult, lesion length of Gd enhancement and T2 lesion contribute to its prediction and a better short-term visual outcome may be associated with detection and localization of Gd enhancement along the optic nerve.
EVALuna2:21236

CD133-Positive Membrane Particles in Cerebrospinal Fluid of Patients with Inflammatory and Degenerative Neurological Diseases - Bobinger, Tobias; May, Lisa-Sophie; Lücking, Hannes; Kloska, Stephan; Burkardt, Petra; Spitzer, Philipp; Maler, Juan M.; Corbeil, Denis; Huttner, Hagen (Frontiers in Cellular Neuroscience, 2017)
Background: Analysis of cerebrospinal fluid (CSF) is a frequently used diagnostic tool in a variety of neurological diseases. Recent studies suggested that investigating membrane particles enriched with the stem cell marker CD133 may offer new avenues for studying neurological disease. In this study, we evaluated the amount of membrane particle-associated CD133 in human CSF in neuroinflammatory and degenerative diseases. Methods: We compared the amount of membrane particle-associated CD133 in CSF samples collected from 45 patients with normal pressure hydrocephalus, parkinsonism, dementia, and cognitive impairment, chronic inflammatory diseases and 10 healthy adult individuals as controls. After ultracentrifugation of CSF, gel electrophoresis and immunoblotting using anti-CD133 monoclonal antibody 80B258 were performed. Antigen-antibody complexes were detected using chemiluminescence. Results: The amount of membrane particle-associated CD133 was significantly increased in patients with normal pressure hydrocephalus (p < 0.001), parkinsonism (p = 0.011) as well as in patients with chronic inflammatory disease (p = 0.008). Analysis of CSF of patients with dementia and cognitive impairment revealed no significant change compared with healthy individuals. Furthermore, subgroup analysis of patients with chronic inflammatory diseases demonstrated significantly elevated levels in individuals with relapsing-remitting multiple sclerosis (p = 0.023) and secondary progressive multiple sclerosis (SPMS; p = 0.010). Conclusion: Collectively, our study revealed elevated levels of membrane particle-associated CD133 in patients with normal pressure hydrocephalus, parkinsonism as well as relapsing-remitting and SPMS. Membrane glycoprotein CD133 may be of clinical value for several neurological diseases.
EVALuna2:22515

Cerebrovascular complications of immunologically mediated heparin-induced thrombocytopenia - Macha, K.; Kloska, Stephan; Dörfler, Arnd; Raaz-Schrauder, D.; Schwab, Sibylle; Köhrmann, Martin; Seifert, Frank (Fortschritte der Neurologie - Psychiatrie, 2014)
Immunologically mediated heparin-induced thrombocytopenia (HIT) is a thrombotic disease caused by antibodies occurring after heparin exposure. Thrombocytopenia occurs within a few days after heparin exposure, about half of HIT-patients develop venous or arterial thrombotic complications. Neurological complications of HIT are mainly ischaemic stroke and sinus vein thrombosis. To ensure the primary clinical diagnosis functional and immunological assays for antibody detection are available. The probability for the occurrence of HIT depends on the nature of heparin employed (LMWH vs. UFH) and individual patient characteristics such as gender and primary disease (medical vs. surgical patients). In the case of suspected HIT heparin administration should be discontinued immediately and replaced by an alternative anticoagulation to prevent the expansion or development of further thrombotic complications. Herein we report a case of a patient suffering from HIT-associated embolic cerebral ischaemic stroke.
EVALuna2:22326

Clinical and radiological outcome after mechanical thrombectomy in acute ischemic stroke: What matters? - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd (Neuroradiology Journal, 2016)
Recent studies have shown the efficacy of mechanical thrombectomy in acute ischemic stroke. We sought to identify prognostic parameters for clinical and radiological outcome after mechanical thrombectomy.In 34 patients (age 72 ± 13 years, 64.7% women) with acute occlusion of the distal ICA and/or M1 segment who were treated with mechanical thrombectomy, the Spearman correlation was performed to assess potential prognostic outcome parameters (age, NIHSS, ASPECT, thrombus length (TL), clot burden score (CBS), relative filling time delay (rFTD), time to recanalization (TTR) and TICI score). The modified Rankin scale (mRS) and the Alberta Stroke Program Early CT (ASPECT) score were used for clinical and radiological outcome, respectively. Receiver operating characteristic (ROC) analysis was performed to assess parameters predicting favorable clinical (?mRS <= 2) and radiological outcome (?ASPECT <= 2).Variables associated with favorable clinical outcome included NIHSS, TL, TTR and TICI score (p <= 0.01) with NIHSS <= 15 (p = 0.001, area under the curve (AUC) 0.87), TL <= 2 cm (p = 0.017, AUC 0.75), TTR <= 231 min (p = 0.001 AUC 0.88) and TICI >= 2b (p = 0.050, AUC 0.70). Shorter TTR and higher TICI scores were associated with favorable radiological outcome (p < 0.001) with TTR <= 224 min (p = 0.023, AUC 0.77) and TICI >= 2b (p = 0.000, AUC 0.86).Fast and complete recanalization is essential to achieve a favorable radiological and functional outcome after mechanical thrombectomy in acute ischemic stroke. Age, CBS and collateral supply play a subordinate role.
EVALuna2:22544

Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
Contradictory results were reported for the outcome after endovascular recanalization (ERT) in acute anterior circulation ischemic stroke. We assessed whether a clinical/perfusion CT cerebral blood volume (CBV) mismatch concept (CPM) can identify patients who will benefit from reperfusion therapy.Imaging and clinical data of 58 consecutive ERT cases with acute anterior circulation stroke (ICA, M1, proximal M2) undergoing intraarterial thrombectomy within 4.5h after symptom onset were analyzed retrospectively. CPM was defined as NIHSS>=8 and PCT CBV ASPECTS>=7. Minor CBV lesion was defined as PCT CBV ASPECTS>=7.All baseline characteristics other than blood glucose did not differ between the paired groups. Revascularization was achieved in 87.9% of all patients without significant difference between the paired groups. Favorable clinical outcome after 3 months (mRS<=2) resulted in 29.3% of all patients, in contrast to 47.4% of the CPM positive and 52.2% of the minor CBV lesion groups.CPM can identify patients who will benefit from reperfusion therapy in acute anterior circulation ischemic stroke.
EVALuna2:14386

Clot Burden and Collaterals in Anterior Circulation Stroke: Differences Between Single-Phase CTA and Multi-phase 4D-CTA - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Siegfried; Dörfler, Arnd (Clinical Neuroradiology, 2014)
It has been reported that the extent of intravascular thrombi and the quality of collateral filling in computed tomography (CT) angiography are predictive for the clinical outcome in patients with acute stroke. We hypothesized that multi-phase four-dimensional CTA (4D-CTA) allows better assessment of clot burden and collateral flow compared with arterial single-phase CTA (CTA).In 49 patients (33 female; age: 77 ± 12 years) with acute anterior circulation stroke, CTA and 4D-CTA reconstructed from dynamic perfusion CT data were analyzed for absolute thrombus length (TL), clot burden score (CBS), and collateral score (CS). The length of the filling defect was also defined on thin-slice nonenhanced CT as corresponding hyperdense middle cerebral artery sign (HMCAS) when present.There was good correlation (r = 0.62, p < 0.01) between the length of HMCAS (1.29 ± 0.62 cm) and TL in 4D-CTA (1.22 ± 0.51 cm). 4D-CTA and CTA significantly varied (p < 0.01) in TL (1.42 ± 0.73 cm (CTA) versus 1.11 ± 0.62 cm (4D-CTA)), CBS (median: 5, interquartile range: 4-7 (CTA) versus median: 6, interquartile range: 5-8 (4D-CTA); p < 0.001), and CS (median: 2, interquartile range: 1-2 (CTA) versus median: 3, interquartile range: 2-3 (4D-CTA); p < 0.001). Accordingly, CTA significantly overrated clot burden and underestimated collateral flow.4D-CTA more closely defines clot burden and collateral supply in anterior circulation stroke than CTA, implicating an additional diagnostic benefit.
EVALuna2:22276

Comparison of conventional CTA and volume perfusion CTA in evaluation of cerebral arterial vasculature in acute stroke - Saake, Marc; Gölitz, Philipp; Struffert, Tobias; Breuer, Lorenz; Volbers, Bastian; Dörfler, Arnd; Kloska, Stephan (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: CTA-like datasets can be reconstructed from whole-brain VPCTA. The aim of our study was to compare VPCTA with CTA for detection of intracranial stenosis and occlusion in stroke patients. Omitting CTA from stroke CT could reduce radiation dose. MATERIALS AND METHODS: One hundred sixty-three patients were included in this retrospective analysis. Inclusion criterion was suspected stroke within 4.5 hours after onset of symptoms. All examinations were performed on a 128-section multidetector CT scanner. Axial, coronal, and sagittal maximum intensity projections were reconstructed from CTA and from peak arterial phase of VPCTA. Images were scored for quality and presence of intracranial stenosis >50% or occlusion. For statistical analysis, the Wilcoxon signed-rank test and Fisher exact test were used, with a 2-tailed P value of .05 or less for statistical significance. RESULTS: Average image quality was superior in CTA (P < .05). However, image quality dichotomized for diagnostic significance was without difference between CTA and VPCTA (P > .05). Comparative statistical analysis revealed no significant difference for detection of intracranial stenosis and occlusion between CTA and VPCTA (P > .05). Substitution of intracranial CTA by VPCTA would lower radiation dose by 0.5 mSv. CONCLUSIONS: VPCTA is suited to assess the intracranial vasculature in patients with stroke and might have the potential to decrease radiation dose by substituting for intracranial CTA in stroke CT. Additional studies are necessary to further evaluate potential benefits of the dynamic nature of VPCTA.
CRIS-Team Scopus Importer:2022-08-05

Comparison of Intracranial Aneurysms Treated by 2-D Versus 3-D Coils: A Matched-Pairs Analysis - Lang, Stefan; Rösch, Julie; Gölitz, Philipp; Kloska, Stephan; Struffert, Tobias; Dörfler, Arnd (Clinical Neuroradiology, 2017)
OBJECTIVE: Knowledge on the influence of 2D and 3D coils to occlude intracranial aneurysms is poor. Therefore, aim of our analysis was to evaluate whether the use of 3-D versus 2-D coils alone may improve the efficacy of endovascular aneurysm treatment. PATIENTS AND METHODS: We performed a matched pair analysis comparing aneurysms treated by 3-D coils as initial "framing" coils to aneurysms treated exclusively by 2-D coils. Number of coils, implanted coil length/volume, and associated packing density were calculated. Aneurysmal occlusion was assessed and monitored 6 months (DSA; magnetic resonance angiography (MRA)) and 18 months (MRA) after embolization. Periprocedural complications and retreatment rate of each group were analyzed. RESULTS: Our retrospective analysis revealed 50 pairs. Concerning the 3-D group, number of coils (353 in total, median 7; p = 0.002), implanted coil length (55.69 ± 48.4 cm), implanted coil length per volume (5.92 mm/mm3), and packing density (30 %; p = 0.017) was higher than in the 2-D group (259 in total, median 5 coils; 38.52 ± 43.13 cm; 4.54 mm/mm3; 23 %). Occlusion was not significantly different immediately after treatment but at 6 and 18 months follow-up in favor of 3-D coils. Retreatment was performed in 2 cases of the 3-D group and in 3 cases of the 2-D group and therefore in a similar range (p = 0.564). CONCLUSION: Initial use of 3-D coils revealed a higher packing density and a higher long-term occlusion. Therefore, we recommend initial use of 3-D coils.
EVALuna2:33475

Correction to: Evaluation After Cochlear Implant Surgery: Correlation of Clinical Outcome and Imaging Findings using Flat-detector CT (Clinical Neuroradiology, (2021), 31, 2, (367-372), 10.1007/s00062-020-00922-1) - Stock, Annika; Bozzato, Victoria; Kloska, Stephan; Bozzato, Alessandro; Hoppe, Ulrich; Hornung, Joachim; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2021)
The article “Evaluation After Cochlear Implant Surgery” written by Annika Stock, Victoria Bozzato, Stephan P. Kloska, Alessandro Bozzato, Ulrich Hoppe, Joachim Hornung, Arnd Dörfler and Tobias Struffert was originally published Online First without Open Access. After publication in volume 31, issue 2, page 367–372 the authors decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made.
CRIS-Team Scopus Importer:2021-09-10

Dynamic Angiography and Perfusion Imaging Using Flat Detector CT in the Angiography Suite: A Pilot Study in Patients with Acute Middle Cerebral Artery Occlusions - Struffert, Tobias; Deuerling-Zheng, Y.; Kloska, Stephan; Engelhorn, Tobias; Lang, Sabine; Mennecke, Angelika; Manhart, M.; Strother, C. M.; Schwab, Sibylle; Dörfler, Arnd (American Journal of Neuroradiology, 2015)
Perfusion and angiographic imaging using intravenous contrast application to evaluate stroke patients is now technically feasible by flat detector CT performed by the angiographic system. The aim of this pilot study was to show the feasibility and qualitative comparability of a novel flat detector CT dynamic perfusion and angiographic imaging protocol in comparison with a multimodal stroke MR imaging protocol.In 12 patients with acute stroke, MR imaging and the novel flat detector CT protocol were performed before endovascular treatment. Perfusion parameter maps (MTT, TTP, CBV, CBF) and MIP/volume-rendering technique images obtained by using both modalities (MR imaging and flat detector CT) were compared.Comparison of MIP/volume-rendering technique images demonstrated equivalent visibility of the occlusion site. Qualitative comparison of perfusion parameter maps by using ASPECTS revealed high Pearson correlation coefficients for parameters CBF, MTT, and TTP (0.95-0.98), while for CBV, the coefficient was lower (0.49).We have shown the feasibility of a novel dynamic flat detector CT perfusion and angiographic protocol for the diagnosis and triage of patients with acute ischemic stroke. In a qualitative comparison, the parameter maps and MIP/volume-rendering technique images compared well with MR imaging. In our opinion, this flat detector CT application may substitute for multisection CT imaging in selected patients with acute stroke so that in the future, patients with acute stroke may be directly referred to the angiography suite, thereby avoiding transportation and saving time.
EVALuna2:22353

Efficacy and safety of combined intraventricular fibrinolysis with lumbar drainage for prevention of permanent shunt dependency after intracerebral hemorrhage with severe ventricular involvement: A randomized trial and individual patient data meta-analysi - Staykov, Dimitre; Kuramatsu, Joji; Bardutzky, Juergen; Volbers, Bastian; Gerner, Stefan; Kloska, Stephan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Annals of Neurology, 2017)
Intraventricular hemorrhage (IVH) is a negative prognostic factor in intracerebral hemorrhage (ICH) and is associated with permanent shunt dependency in a substantial proportion of patients post-ICH. IVH treatment by intraventricular fibrinolysis (IVF) was recently linked to reduced mortality rates in the CLEAR III study and IVF represents a safe and effective strategy to hasten clot resolution that may reduce shunt rates. Additionally, promising results from observational studies reported reductions in shunt dependency for a combined treatment approach of IVF plus lumbar drains (LDs). The present randomized, controlled trial investigated efficacy and safety of a combined strategy-IVF plus LD versus IVF alone-on shunt dependency in patients with ICH and severe IVH.This randomized, open-label, parallel-group study included patients aged 18 to 85 years, prehospital modified Rankin Scale <=3, ICH volume < 60ml, Glasgow Coma Scale of <9, and severe IVH with tamponade of the third and fourth ventricles requiring placement of external ventricular drainage (EVD). Over a 3-year recruitment period, patients were allocated to either standard treatment (control group receiving IVF consisting of 1mg of recombinant human tissue plasminogen activator every 8 hours until clot clearance of third and fourth ventricles) or a combined treatment approach of IVF and-upon clot clearance of third and fourth ventricles-subsequent placement of an LD for drainage of cerebrospinal fluid (CSF; intervention group). The primary endpoint consisted of permanent shunt placement indicated after a total of three unsuccessful EVD clamping attempts or need for CSF drainage longer than 14 days in both groups. Secondary endpoints included IVF- and LD-related safety, such as bleeding or infections, and functional outcome at 90 and 180 days. Conducted endpoint analyses used individual patient data meta-analyses. The study was registered at clinicaltrials.gov (NCT01041950).The trial was stopped upon predefined interim analysis after 30 patients because of significant efficacy of tested intervention. The primary endpoint was analyzed without dropouts and was reached in 43% (7 of 16) of the control group versus 0% (0 of 14) of the intervention group (p = 0.007). Meta-analyses were based on overall 97 patients, 45 patients receiving IVF plus LD versus 42 with IVF only. Meta-analyses on shunt dependency showed an absolute risk reduction of 24% for the intervention (LD, 2.2% [1 of 45] vs no-LD, 26.2% [11 of 42]; odds ratio [OR] = 0.062; confidence interval [CI], 0.011-0.361; p = 0.002). Secondary endpoints did not show significant differences for CSF infections (OR = 0.869;CI, 0.445-1.695; p = 0.680) and functional outcome at 90 days (OR = 0.478; CI, 0.190-1.201; p = 0.116), yet bleeding complications were significantly reduced in favor of the intervention (OR = 0.401; CI, 0.302-0.532; p < 0.001).The present trial and individual patient data meta-analyses provide evidence that, in patients with severe IVH, as compared to IVF alone, a combined approach of IVF plus LD treatment is feasible and safe and significantly reduces rates of permanent shunt dependency for aresorptive hydrocephalus post-ICH. ANN NEUROL 2017;81:93-103.
EVALuna2:22478

Erratum to 'Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke' (Clinical Neurology and Neurosurgery (2014) 121, (39-45)) - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
CRIS-Team Scopus Importer:2022-08-05

Evaluation After Cochlear Implant Surgery: Correlation of Clinical Outcome and Imaging Findings using Flat-detector CT - Stock, Annika; Bozzato, Victoria; Kloska, Stephan; Bozzato, Alessandro; Hoppe, Ulrich; Hornung, Joachim; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2020)
Purpose: Assessment of the cochlear implant (CI) electrode array position using flat-detector computed tomography (FDCT) to test dependence of postoperative outcome on intracochlear electrode position. Methods: A total of 102 patients implanted with 107 CIs underwent FDCT. Electrode position was rated as 1) scala tympani, 2) scala vestibuli, 3) scalar dislocation and 4) no deconvolution. Two independent neuroradiologists rated all image data sets twice and the scalar position was verified by a third neuroradiologist. Presurgical and postsurgical speech audiometry by the Freiburg monosyllabic test was used to evaluate auditory outcome after 6 months of speech rehabilitation. Results: Electrode array position was assessed by FDCT in 107 CIs. Of the electrodes 60 were detected in the scala tympani, 21 in the scala vestibuli, 24 electrode arrays showed scalar dislocation and 2 electrodes were not placed in an intracochlear position. There was no significant difference in rehabilitation outcomes between scala tympani and scala vestibuli inserted patients. Rehabilitation was also possible in patients with dislocated electrodes. Conclusion: The use of FDCT is a reliable diagnostic method to determine the position of the electrode array. In our study cohort, the electrode position had no significant impact on postoperative outcome except for non-deconvoluted electrode arrays.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Cochlear implantation; Deafness; Dyna-CT; Misplaced cochlear implant electrode array; Rehabilitation

Fatal lymphomatoid granulomatosis with primary CNS-involvement in an immunocompetent 80-year-old woman - Olmes, David G.; Agaimy, Abbas; Kloska, Stephan; Linker, Ralf (BMJ Case Reports, 2014)
An 80-year-old woman presented with weight loss, fatigue, dizziness and a brain stem lesion. Extensive work-up revealed lymphomatoid granulomatosis (LYG) with primary clinical manifestation in the central nervous system (CNS), a rare Epstein-Barr virus-driven multisystem lymphoproliferative disorder, to be causative for the symptoms. Immunochemotherapy consisting of rituximab and temozolomide was started, but the disease progressed and the patient subsequently died. Histology, diagnostic criteria, differential diagnosis and treatment options for LYG with CNS involvement are discussed. This case demonstrates that LYG with CNS involvement may necessitate more aggressive treatment approaches than combination therapy with rituximab and temozolomide.
EVALuna2:6736

Feasibility of cerebral blood volume mapping by flat panel detector CT in the angiography suite: First experience in patients with acute middle cerebral artery occlusions - Struffert, Tobias; Deuerling-Zheng, Y.; Engelhorn, Tobias; Kloska, Stephan; Gölitz, Philipp; Koehrmann, M.; Schwab, S.; Strother, C. M.; Dörfler, Arnd (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: A new FPCT application offers the possibility of perfusion (FPCT CBV) and parenchymal (FPCT) imaging within the angiography suite. We tested the hypothesis that findings in FPCT CBV and FPCT would correlate with those obtained using MSCT and PCT. MATERIALS AND METHODS: In 16 patients with acute MCA occlusion, FPCT CBV was performed immediately posttreatment. The volume of tissue having abnormal CBV values was determined by FPCT CBV and PCT images. Stroke volume on follow-up MSCT was determined, CBV values in the effected parenchyma were measured, and FPCT images were reviewed. RESULTS: In 6 cases, we found a FPCT CBV value identical or higher (hyperemia) in comparison with the contralateral side. In 10 cases, we found CBV lesions with values lower (oligemia) than the contralateral brain tissue. We found a high correlation of CBV lesion volume on FPCT CBV images to stroke volume on follow-up MSCT (r = 0.9, P < .05) in the oligemia group. Absolute FPCT CBV and PCT CBV values were comparable and showed good correlation (r = 0.9, P < .05). In 8 patients, contrast medium extravasation was visible. CONCLUSIONS: The new FPCT application allows assessment of CBV in acute stroke patients. Our initial results indicate that these measurements may predict final infarct volume. The ability to assess this key parameter of cerebral perfusion within the angiographic suite may improve the management of these patients.
CRIS-Team Scopus Importer:2022-08-05

Fibrinolysis Treatment for Cerebral Intraventricular Hemorrhage: A Temporal and Spatial Voxel-Based Analysis - Strinitz, Marc; Kuramatsu, Joji; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Seifert, Frank (Journal of Neuroimaging, 2016)
A voxel-based statistical approach on computer tomographic data in patients with intracerebral hemorrhage (ICH) and acute intraventricular hemorrhage (IVH) was used to evaluate spatial and temporal patterns of intraventricular blood in patients treated with intraventricular fibrinolysis (IVF) or without.IVH shapes were systematically assessed three dimensionally in patients with supratentorial ICH at three intervals of time (day of admission, day 4 ± 1, day 7+). The boundaries of the intraventricular blood clot were delineated on computed tomography (CT) scans using dedicated software. The CT scan and the IVH shape were transferred into stereotaxic space. In a second step, voxel-based statistics on group level were used to correlate the distribution of intraventricular blood with the interval and the treatment group.Altogether 45 patients, 29 with IVF therapy and 16 without, were eligible to be included into this study. We found significant (false discovery rate [FDR] correction, q < .05) reduction of the intraventricular blood between day of admission and day 7 + for the third and fourth ventricle and parts of both lateral ventricles. In addition, we were able to show a significant difference between the IVF therapy and the conventionally treated group at day 4 ± 1 for the third ventricle.The data indicate that voxel-based analysis on group level can be used to compare the time course and the distribution of intraventricular hemorrhage. This technique could be an interesting tool for future research on ICH with IVH.
EVALuna2:22457

FLAIRfusion Processing with Contrast Inversion : Improving Detection and Reading Time of New Cerebral MS Lesions - Schmidt, Manuel; Linker, Ralf; Lang, S.; Lücking, Hannes; Engelhorn, Tobias; Kloska, Stephan; Uder, Michael; Dörfler, Arnd; Dankerl, Peter; Cavallaro, Alexander Josef (Clinical Neuroradiology, 2017)
To evaluate the performance of an innovative image processing approach for detection of T2-weighted hyperintense multiple sclerosis (MS) lesions.In this study 20 consecutive patients with inflammatory demyelinating lesions were retrospectively evaluated of whom 10 patients featured progressive disease and 10 a stable lesion load. 3 mm transversal FLAIRfusion imaging was processed and archived. Image processing was performed through landmark-based 3D co-registration of the previous and current isotropic FLAIR examination followed by inversion of image contrast. Thereby, the hyperintense signals of the unchanged MS plaques extinguish each other, while newly developed lesions appear bright on FLAIRfusion. Diagnostic performance was evaluated by 4 experienced readers. Consensus reading supplied the reference standard. Sensitivity, specificity, NPV (negative predictive value), PPV (positive predictive value), interreader agreement and reading time were the outcome measures analyzed.Combined sensitivity was 100% at a specificity of 88.2%, with PPV ranging from 83.3% to 90.1% and NPV at 100%. Reading time was nearly 5-fold faster than conventional side by side comparison (35.6 s vs. 163.7 s, p < 0.001). Cohen's kappa was excellent (>0.75; p < 0.001) and Cronbach's alpha was 0.994.FLAIRfusion provides reliable detection of newly developed MS lesions along with strong interreader agreement across all levels of expertise in 35 s of reading time.
EVALuna2:14615

Flat-Panel Computed Tomography (DYNA-CT) in Neuroradiology. From High-Resolution Imaging of Implants to One-Stop-Shopping for Acute Stroke - Dörfler, Arnd; Gölitz, Philipp; Engelhorn, Tobias; Kloska, Stephan; Struffert, Tobias (Clinical Neuroradiology, 2015)
Originally aimed at improving standard radiography by providing higher absorption efficiency and a wider dynamic range, flat-panel detector technology has meanwhile got widely accepted in the neuroradiological community. Especially flat-panel detector computed tomography (FD-CT) using rotational C-arm mounted flat-panel detector technology is capable of volumetric imaging with a high spatial resolution. By providing CT-like images of the brain within the angio suite, FD-CT is able to rapidly visualize hemorrhage and may thus improve complication management without the need of patient transfer. As "Angiographic CT" FD-CT may be helpful during many diagnostic and neurointerventional procedures and for noninvasive monitoring and follow-up. In addition, spinal interventions and high-resolution imaging of the temporal bone might also benefit from FD-CT. Finally, using novel dynamic perfusion and angiographic protocols, FD-CT may provide functional information on brain perfusion and vasculature with the potential to replace standard imaging in selected acute stroke patients.
EVALuna2:22997

FRED Flow Diverter: A Study on Safety and Efficacy in a Consecutive Group of 50 Patients - Lücking, Hannes; Engelhorn, Tobias; Lang, Stefan; Gölitz, Philipp; Kloska, Stephan; Roessler, Karl; Dörfler, Arnd (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Endovascular flow diverters are increasingly used for the treatment of cerebral aneurysms. We assessed the safety and efficacy of the Flow-Redirection Endoluminal Device (FRED) in a consecutive series of 50 patients. MATERIALS AND METHODS: Inclusion criteria were wide-neck, blister-like, or fusiform/dissecting aneurysms independent of size, treated with the FRED between February 2014 and May 2015. Assessment criteria were aneurysm occlusion, manifest ischemic stroke, bleeding, or death. The occlusion rate was assessed at 3 months with flat panel CT and at 6 months with DSA by using the Raymond classification and the O'Kelly-Marotta grading scale. RESULTS: Fifty patients with 52 aneurysms were treated with 54 FREDs; 20 patients were treated with the FRED and coils. Aneurysm size ranged from 2.0 to 18.5 mm. Deployment of the FRED was successful in all cases. There were no device-associated complications. One patient developed mild stroke symptoms that fully receded within days. There have been no late-term complications so far and no treatment-related mortality. Initial follow-up at 3 months showed complete occlusion in 72.3% of the overall study group, Six-month follow-up showed total and remnant-neck occlusion in 87.2% of patients, distributed over 81.5% of the FRED-only cases and 95.0% of the cases with combined treatment. CONCLUSIONS: The FRED flow diverter is a safe device for the treatment of cerebral aneurysms of various types. Our data reveal high occlusion rates at 3 and 6 months, comparable with those in other flow diverters. Long-term occlusion rates are expected.
EVALuna2:33142

Functional Long-Term Outcome after Left- versus Right-Sided Intracerebral Hemorrhage - Beuscher, Vanessa D.; Kuramatsu, Joji; Gerner, Stefan; Kohn, Julia; Lücking, Hannes; Kloska, Stephan; Huttner, Hagen (Cerebrovascular Diseases, 2017)
Hemispheric location might influence outcome after intracerebral hemorrhage (ICH). INTERACT suggested higher short-term mortality in right hemispheric ICH, yet statistical imbalances were not addressed. This study aimed at determining the differences in long-term functional outcome in patients with right- vs. left-sided ICH with a priori-defined sub-analysis of lobar vs. deep bleedings.Data from a prospective hospital registry were analyzed including patients with ICH admitted between January 2006 and August 2014. Data were retrieved from institutional databases. Outcome was assessed using the modified Rankin Scale (mRS) score. Outcome measures (long-term mortality and functional outcome at 12 months) were correlated with ICH location and hemisphere, and the imbalances of baseline characteristics were addressed by propensity score matching.A total of 831 patients with supratentorial ICH (429 left and 402 right) were analyzed. Regarding clinical baseline characteristics in the unadjusted overall cohort, there were differences in disfavor of right-sided ICH (antiplatelets: 25.2% in left ICH vs. 34.3% in right ICH; p < 0.01; previous ischemic stroke: 14.7% in left ICH vs. 19.7% in right ICH; p = 0.057; and presence/extent of intraventricular hemorrhage: 45.0% in left ICH vs. 53.0% in right ICH; p = 0.021; Graeb-score: 0 [0-4] in left ICH vs. 1 [0-5] in right ICH; p = 0.017). While there were no differences in mortality and in the proportion of patients with favorable vs. unfavorable outcome (mRS 0-3: 142/375 [37.9%] in left ICH vs. 117/362 [32.3%] in right ICH; p = 0.115), patients with left-sided ICH showed excellent outcome more frequently (mRS 0-1: 64/375 [17.1%] in left ICH vs. 43/362 [11.9%] in right ICH; p = 0.046) in the unadjusted analysis. After adjusting for confounding variables, a well-balanced group of patients (n = 360/hemisphere) was compared showing no differences in long-term functional outcome (mRS 0-3: 36.4% in left ICH vs. 33.9% in right ICH; p = 0.51). Sub-analyses of patients with deep vs. lobar ICH revealed also no differences in outcome measures (mRS 0-3: 53/151 [35.1%] in left deep ICH vs. 53/165 [32.1%] in right deep ICH; p = 0.58).Previously described differences in clinical end points among patients with left- vs. right-hemispheric ICH may be driven by different baseline characteristics rather than by functional deficits emerging from different hemispheric functions affected. After statistical corrections for confounding variables, there was no impact of hemispheric location on functional outcome after ICH.
EVALuna2:22480

Hyponatremia is an independent predictor of in-hospital mortality in spontaneous intracerebral hemorrhage - Kuramatsu, Joji; Bobinger, Tobias; Volbers, Bastian; Staykov, Dimitre; Lücking, Hannes; Kloska, Stephan; Köhrmann, Martin; Huttner, Hagen (Stroke, 2014)
Hyponatremia is the most frequent electrolyte disturbance in critical care. Across various disciplines, hyponatremia is associated with increased mortality and longer hospital stay, yet in intracerebral hemorrhage (ICH) no data are available. This the first study that investigated the prevalence and clinical associations of hyponatremia in patients with ICH.This observational study included all consecutive spontaneous ICH patients (n=464) admitted during a 5-year period to the Department of Neurology. Patient characteristics, in-hospital measures, mortality, and functional outcome (90 days and 1 year) were analyzed to determine the effects of hyponatremia (Na<135 mEq/L). Multivariable regression analyses were calculated for factors associated with hyponatremia and predictors of in-hospital mortality.The prevalence of hyponatremia on hospital admission was 15.6% (n=66). Normonatremia was achieved and maintained in almost all hyponatremia patients<48 hours. In-hospital mortality was roughly doubled in hyponatremia compared with nonhyponatremia patients (40.9%; n=27 versus 21.1%; n=75), translating into a 2.5-fold increased odds ratio (P<0.001). Multivariable analyses identified hyponatremia as an independent predictor of in-hospital mortality (odds ratio, 2.2; 95% confidence interval, 1.05-4.62; P=0.037). Within 90 days after ICH, hyponatremia patients surviving hospital stay were also at greater risk of death (odds ratio, 4.8; 95% confidence interval, 2.1-10.6; P<0.001); thereafter, mortality rates were similar.Hyponatremia was identified as an independent predictor of in-hospital mortality with a fairly high prevalence in spontaneous ICH patients. The presence of hyponatremia at hospital admission is related to an increased short-term mortality in patients surviving acute care, possibly reflecting a preexisting condition that is linked to worse outcome due to greater comorbidity. Correction of hyponatremia does not seem to compensate its influence on mortality, which strongly warrants future research.
EVALuna2:22304

Impact of Hypothermia Initiation and Duration on Perihemorrhagic Edema Evolution After Intracerebral Hemorrhage - Volbers, Bastian; Herrmann, Sabrina; Willfarth, Wolfgang; Lücking, Hannes; Kloska, Stephan; Dörfler, Arnd; Huttner, Hagen; Kuramatsu, Joji; Schwab, Stefan; Staykov, Dimitre (Stroke, 2016)
Intracerebral hemorrhage (ICH) causes high morbidity and mortality. Recently, perihemorrhagic edema (PHE) has been suggested as an important prognostic factor. Therapeutic hypothermia may be a promising therapeutic option to treat PHE. However, no data exist about the optimal timing and duration of therapeutic hypothermia in ICH. We examined the impact of therapeutic hypothermia timing and duration on PHE evolution.In this retrospective, single-center, case-control study, we identified patients with ICH treated with mild endovascular hypothermia (target temperature 35°C) from our institutional database. Patients were grouped according to hypothermia initiation (early: days 1-2 and late: days 4-5 after admission) and hypothermia duration (short: 4-8 days and long: 9-15 days). Patients with ICH matched for ICH volume, age, ICH localization, and intraventricular hemorrhage were identified as controls. Relative PHE, temperature, and intracranial pressure course were analyzed. Clinical outcome on day 90 was assessed using the modified Rankin scale (0-3=favorable and 4-6=poor).Thirty-three patients with ICH treated with hypothermia and 37 control patients were included. Early hypothermia initiation led to relative PHE decrease between admission and day 3, whereas median relative PHE increased in control patients (-0.05 [interquartile range, -0.4 to 0.07] and 0.07 [interquartile range, -0.07 to 0.26], respectively; P=0.007) and patients with late hypothermia initiation (0.22 [interquartile range 0.12-0.27]; P=0.037). After day 3, relative PHE increased in all groups without difference. Outcome was not different between patients treated with hypothermia and controls.Early hypothermia initiation after ICH onset seems to have an important impact on PHE evolution, whereas our data suggest only limited impact later than day 3 after onset.
EVALuna2:22477

Intraventricular fibrinolysis has no effects on shunt dependency and functional outcome in endovascular-treated aneurysmal SAH - Gerner, Stefan; Kuramatsu, Joji; Abel, Henning; Kloska, Stephan; Lücking, Hannes; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Neurocritical Care, 2014)
Intraventricular fibrinolysis (IVF) in subarachnoid hemorrhage (SAH) is an emerging strategy aiming to hasten clot lysis, treat hydrocephalus, and reduce permanent shunt rates. Because of clinical heterogeneity of investigated patient effects of IVF on permanent shunt incidence and functional outcome are widely debated. The present study is the first to investigate solely endovascular-treated SAH patients.Overall, 88 consecutive patients with aneurysmal SAH requiring external ventricular drain placement and endovascular aneurysm closure were included. Functional outcome and shunt dependency were assessed 90 days after event. A matched controlled sub-analysis was carried out to investigate the effects of IVF treatment (n = 14; matching criteria: age, neuro-status and imaging). Multivariate modeling was performed to identify independent predictors for permanent shunt dependency.In IVF-patients neurological status was significantly poorer [Hunt&Hess: IVF = 4(3-5) vs. non-IVF = 3(1-5); p = 0.035] and the extent of ventricular hemorrhage was increased [Graeb Score: IVF = 7(6-8) vs. non-IVF = 3(1-4); p <= 0.001]. Consecutive matched controlled sub-analysis revealed no significant therapeutic effect of IVF with respect to shunt dependency rate and functional outcome. Multivariate analysis revealed Graeb score [OR = 1.34(1.02-1.76); p = 0.035] and sepsis [OR = 11.23(2.28-55.27); p = 0.003] as independent predictors for shunt dependency, whereas IVF did not exert significant effects (p = 0.820).In endovascular-treated SAH patients IVF neither reduced permanent shunt dependency nor influenced functional outcome. Despite established effects on intraventricular clot resolution IVF appears less powerful in SAH as compared to ICH. Given the reported positive effects of lumbar drainage (LD) in SAH, a prospective analysis of a combined treatment approach of IVF and subsequent lumbar drain sOeems warranted aiming to reduce permanent shunting and improve functional outcome.
EVALuna2:22283

Is Hypothermia Helpful in Severe Subarachnoid Hemorrhage? An Exploratory Study on Macro Vascular Spasm, Delayed Cerebral Infarction and Functional Outcome after Prolonged Hypothermia - Kuramatsu, Joji; Kollmar, Rainer; Gerner, Stefan; Madzar, Dominik; Pisarcikova, Andrea; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (Cerebrovascular Diseases, 2015)
Therapeutic hypothermia (TH) is an established treatment after cardiac arrest and growing evidence supports its use as neuroprotective treatment in stroke. Only few and heterogeneous studies exist on the effect of hypothermia in subarachnoid hemorrhage (SAH). A novel approach of early and prolonged TH and its influence on key complications in poor-grade SAH, vasospasm and delayed cerebral ischemia (DCI) was evaluated.This observational matched controlled study included 36 poor-grade (Hunt and Hess Scale >3 and World Federation of Neurosurgical Societies Scale >3) SAH patients. Twelve patients received early TH (<48 h after ictus), mild (35°C), prolonged (7 ± 1 days) and were matched to 24 patients from the prospective SAH database. Vasospasm was diagnosed by angiography, macrovascular spasm serially evaluated by Doppler sonography and DCI was defined as new infarction on follow-up CT. Functional outcome was assessed at 6 months by modified Rankin Scale (mRS) and categorized as favorable (mRS score 0-2) versus unfavorable (mRS score 3-6) outcome.Angiographic vasospasm was present in 71.0% of patients. TH neither influenced occurrence nor duration, but the degree of macrovascular spasm as well as peak spastic velocities were significantly reduced (p < 0.05). Frequency of DCI was 87.5% in non-TH vs. 50% in TH-treated patients, translating into a relative risk reduction of 43% and preventive risk ratio of 0.33 (95% CI 0.14-0.77, p = 0.036). Favorable functional outcome was twice as frequent in TH-treated patients 66.7 vs. 33.3% of non-TH (p = 0.06).Early and prolonged TH was associated with a reduced degree of macrovascular spasm and significantly decreased occurrence of DCI, possibly ameliorating functional outcome. TH may represent a promising neuroprotective therapy possibly targeting multiple pathways of DCI development, notably macrovascular spasm, which strongly warrants further evaluation of its clinical impact.
EVALuna2:22357

Lesion mapping of stroke-related erectile dysfunction - Winder, Klemens; Seifert, Frank; Köhrmann, Martin; Crodel, Carl; Kloska, Stephan; Dörfler, Arnd; Hoesl, Katharina M.; Schwab, Stefan; Hilz, Max-Josef (Brain, 2017)
Acute ischaemic stroke in brain areas contributing to male sexual function may impair erectile function depending on the lesion site. This study intended to determine associations between stroke-related erectile dysfunction and cerebral ischaemic lesion sites using voxel-based lesion mapping. In 52 males (mean age 60.5 ± 10.5 years) with first-ever ischaemic strokes, we assessed erectile function after and retrospectively 3 months prior to the stroke using scores of the 5-item International Index of Erectile Function-5 questionnaire. We assessed cardiovascular risk factors and determined clinical stroke severity and infarct volumes as well as total brain volume by neuroimaging. We calculated correlations between patient age, clinical stroke severity, infarct volumes as well as brain volumes and the difference between erectile dysfunction scores before and after stroke. Moreover, we compared patient age, prevalence of cardiovascular risk factors, clinical stroke severity, infarct volumes and brain volumes of patients with unchanged and deteriorated erectile function after stroke. The infarcts were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed subtraction analyses of lesions. In a voxel-based lesion analysis, the difference between erectile dysfunction scores before and after stroke was correlated with the lesion site using t-test statistics. Finally, we conducted a region of interest-based multivariate linear regression analysis that was adjusted for potential confounding factors including patient age, clinical stroke severity, imaging modality, lesion size and brain volume. In 32 patients (61.5%) erectile dysfunction scores declined after the stroke and therefore had stroke-related erectile dysfunction. Deterioration of erectile dysfunction scores was not associated with patient age, clinical stroke severity, infarct volume, brain volume, and cardiovascular risk factors. The voxel-wise subtraction analysis showed associations between stroke-related erectile dysfunction and lesion sites in the right occipito-parietal cortex and thalamus, as well as in the left insula and adjacent temporo-parietal areas. Using voxel-wise t-test statistics, we showed associations between deterioration of erectile function and lesion sites in the right occipital and thalamic region, and the left parietal association area. The linear regression analysis showed that stroke-related erectile dysfunction remained associated with lesions of the right occipital and left parietal association areas after adjusting for confounding factors. In conclusion, our voxel-wise analysis indicates that deteriorating erectile function after stroke is associated with lesions in the right occipito-parietal and thalamic areas integrating visual and somatosensory information, as well as lesions in the left insular and adjacent parieto-temporal areas contributing to generating and mapping visceral arousal states.
EVALuna2:22497

Limited versus Whole-Brain Perfusion for the Indication of Thrombolysis in the Extended Time Window of Acute Cerebral Ischemia - Breuer, Lorenz; Knott, Michael; Struffert, Tobias; Kloska, Stephan; Kurka, Natalia; Schwab, Stefan; Dörfler, Arnd; Köhrmann, Martin; Engelhorn, Tobias (Journal of Stroke and Cerebrovascular Diseases, 2015)
Perfusion computed tomography (PCT) has emerged as alternative to magnetic resonance imaging (MRI) for assessment of patients clinically qualifying for off-label thrombolysis within 4.5 to 9 hours after onset of ischemic stroke. However, disadvantage of PCT is its often limited anatomic coverage with only 2 or 3 slices when using a 4- to 64-section scanner. Our purpose was therefore to evaluate the value of 2- and 3-slice perfusion compared to whole-brain perfusion.One hundred twenty-five patients undergoing MRI beyond 4.5 hours after symptom onset with supratentorial perfusion deficit were selected retrospectively. Accordingly to PCT slice positioning, 2 or 3 slices of the whole-brain perfusion weighted imaging data set were depicted. Volumes of infarct (using cerebral blood volume) and penumbra (using time-to-peak and cerebral blood volume) were calculated, and results were compared with 2- and 3-slice-derived volumes, respectively.Whole-brain imaging revealed a mismatch of more than 20% in 68.8% of patients (defined as 100%). Two-slice imaging detected a perfusion deficit in 72% and a mismatch in 48.8% (sensitivity = 70.9%). Three-slice imaging detected a perfusion deficit in 76% and a mismatch in 50.4% (sensitivity = 73.3%). Although there was no significant difference between 2- and 3-slice imaging (P > .23), both techniques revealed significantly less patients with mismatch compared to whole-brain coverage (P < .01).Two- and 3-slice imaging like obtained with PCT on most installed CT systems to assess perfusion deficits with subsequent mismatch calculation in acute stroke outside the 4.5-hour time window is significantly inferior to whole-brain coverage and, hence, has to be considered as a less-than-ideal solution.
EVALuna2:22358

Lymphocytopenia Is an Independent Predictor of Unfavorable Functional Outcome in Spontaneous Intracerebral Hemorrhage - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Madzar, Dominik; Sembill, Jochen; Lücking, Hannes; Kloska, Stephan; Keil, Toni; Kuramatsu, Joji; Huttner, Hagen (Stroke, 2016)
Stroke-associated immunosuppression is an increasingly recognized factor triggering infections and thus potentially influencing outcome after stroke. Specifically, lymphocytopenia after intracerebral hemorrhage (ICH) has only been addressed in small-sized retrospective studies of mixed intracranial bleedings. This cohort study investigated the natural course of lymphocytopenia, parameters associated with lymphocytopenia on admission (LOA) and during stay, and evaluated the clinical impact of lymphocytopenia in solely ICH patients.This observational study included 855 consecutive patients with ICH. Patient demographics, clinical and neuroradiological data as well as laboratory and in-hospital measures were retrieved from institutional prospective databases. Functional 3-month outcome was assessed by mailed questionnaires. Lymphocytopenia was defined as <1.0 (10(9)/L) and was correlated with patient's characteristics and outcome.Prevalence of LOA was 27.3%. Patients with LOA showed significant associations with poorer neurological status (18 [10-32] versus 13 [5-24]; P<0.001), larger hematoma volume (18.5 [6.2-46.2] versus 12.8 [4.4-37.8]; P=0.006), and unfavorable outcome (74.7% versus 63.3%; P=0.0018). Natural course of lymphocyte count during hospital stay revealed a lymphocyte nadir of 1.1 (0.80-1.53 [10(9)/L]) at day 5. Focusing on patients with day-5-lymphocytopenia, compared with patients with LOA, revealed increased rates of infections (63 [71.6] versus 113 [48.5]; P<0.001) and poorer functional outcome at 3 months (76 [86.4] versus 175 [75.1); P=0.029). Adjusting for baseline confounders, multivariable logistic and receiver operating characteristics analyses documented independent associations of day-5-lymphocytopenia with unfavorable outcome (day-5-lymphocytopenia: odds ratio, 2.017 [95% confidence interval, 1.029-3.955], P=0.041; LOA: odds ratio, 1.391 [0.795-2.432], P=0.248; receiver operating characteristics: day-5-lymphocytopenia: area under the curve=0.673, P<0.0001, Youden's index=0.290; LOA: area under the curve=0.513, P=0.676, Youden's index=0.084), whereas receiver operating characteristics analyses revealed no association of age or hematoma volume with day-5-lymphocytopenia (age: area under the curve=0.540, P=0.198, Youden's index=0.106; volume: area under the curve=0.550, P=0.0898, Youden's index=0.1224).Lymphocytopenia is frequently present in patients with ICH and may represent an independent parameter associated with unfavorable functional outcome. Developing lymphocytopenia affected outcome even stronger than LOA, a finding that may open up new therapeutic avenues in specific subsets of patients with ICH.
EVALuna2:22442

Meningioma growth dynamics assessed by radiocarbon retrospective birth dating - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; El Cheikh, Raouf; Nakamura, Makoto; Tortora, Angelo; Heinke, Paula; Coras, Roland; Englund, Elisabet; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Röder, Sebastian; et al. (EBioMedicine, 2018)
It is not known how long it takes from the initial neoplastic transformation of a cell to the detection of a tumor, which would be valuable for understanding tumor growth dynamics. Meningiomas show a broad histological, genetic and clinical spectrum, are usually benign and considered slowly growing. There is an intense debate regarding their age and growth pattern and when meningiomas should be resected. We have assessed the age and growth dynamics of 14 patients with meningiomas (WHO grade I: n=6 with meningothelial and n=6 with fibrous subtype, as well as n=2 atypical WHO grade II meningiomas) by combining retrospective birth-dating of cells by analyzing incorporation of nuclear-bomb-test-derived 14C, analysis of cell proliferation, cell density, MRI imaging and mathematical modeling. We provide an integrated model of the growth dynamics of benign meningiomas. The mean age of WHO grade I meningiomas was 22.1±6.5years, whereas atypical WHO grade II meningiomas originated 1.5±0.1years prior to surgery (p<0.01). We conclude that WHO grade I meningiomas are very slowly growing brain tumors, which are resected in average two decades after time of origination.
EVALuna2:34031

Monitoring of balloon test occlusion of the internal carotid artery by parametric color coding and perfusion imaging within the angio suite: first results - Struffert, Tobias; Deuerling-Zheng, Y.; Engelhorn, Tobias; Kloska, Stephan; Gölitz, Philipp; Bozzato, A.; Kapsreiter, M.; Strother, C. M.; Dörfler, Arnd (Clinical Neuroradiology, 2013)
Temporary balloon test occlusion (BTO) might be performed prior to procedures in which occlusion of the internal carotid artery (ICA) might be necessary. We tested the hypothesis that parametric color coding (PCC) of angiographic series (digital subtraction angiography (DSA)) along with the assessment of cerebral blood volume (CBV) in the angiography suite would simplify and enhance the identification of candidates who are most likely to tolerate occlusion.Fifteen patients underwent angiographic series (DSA) and perfusion imaging before and during BTO. Pre- and postocclusion DSA acquisitions were evaluated for venous delay by conventional methods ("eye balling") and by PCC measurements. Comparison of CBV values between the left and right hemisphere in 6 defined regions was performed.Values of venous delay by eye balling and PCC showed a high correlation (r = 0.87, p < 0.01). Bland-Altman plot indicated slightly lower values (-0.05 s) by the PCC method. One of the 15 patients developed an asymmetrical CBV map with an increase in CBV of more than one standard deviation in 3 of the 6 regions of interest (ROIs). Acquisition of angiographic series and perfusion imaging did not prolong the test occlusion time.PCC and CBV mapping are feasible during BTO. The use of PCC seems to simplify the ability to measure changes in venous filling delay. Perfusion imaging may show an increase in CBV in patients reaching the limits of cerebral autoregulation. These patients may be at risk for delayed infarction, even though they seem to tolerate temporary occlusion, and could be unsuitable candidates for permanent ICA occlusion.
EVALuna2:22981

Neuroanatomical correlates of severe cardiac arrhythmias in acute ischemic stroke - Seifert, Frank; Kallmünzer, Bernd; Gutjahr, Isabell; Breuer, Lorenz; Winder, Klemens; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Journal of Neurology, 2015)
Neurocardiological interactions can cause severe cardiac arrhythmias in patients with acute ischemic stroke. The relationship between the lesion location in the brain and the occurrence of cardiac arrhythmias is still discussed controversially. The aim of the present study was to correlate the lesion location with the occurrence of cardiac arrhythmias in patients with acute ischemic stroke. Cardiac arrhythmias were systematically assessed in patients with acute ischemic stroke during the first 72 h after admission to a monitored stroke unit. Voxel-based lesion-symptom mapping (VLSM) was used to correlate the lesion location with the occurrence of clinically relevant severe arrhythmias. Overall 150 patients, 56 with right-hemispheric and 94 patients with a left-hemispheric lesion, were eligible to be included in the VLSM study. Severe cardiac arrhythmias were present in 49 of these 150 patients (32.7%). We found a significant association (FDR correction, q < 0.05) between lesions in the right insular, right frontal and right parietal cortex as well as the right amygdala, basal ganglia and thalamus and the occurrence of cardiac arrhythmias. Because left- and right-hemispheric lesions were analyzed separately, the significant findings rely on the 56 patients with right-hemispheric lesions. The data indicate that these areas are involved in central autonomic processing and that right-hemispheric lesions located to these areas are associated with an elevated risk for severe cardiac arrhythmias.
EVALuna2:22355

Neuroanatomic correlates of poststroke hyperglycemia - Winder, Klemens; Seifert, Frank; Ohnemus, Tessa; Sauer, Eva-Maria; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Annals of Neurology, 2015)
A study was undertaken to determine associations between ischemic stroke sites and poststroke hyperglycemia (PSH).Nondiabetic patients with first ever ischemic stroke confirmed by imaging were prospectively included. Blood glucose level (BGL), National Institute of Health Stroke Scale (NIHSS) score, and clinical parameters were assessed on admission. BGL was dichotomized for elevated versus normal levels using a cutoff value of >7.0 mmol/l. Clinical parameters were correlated with BGL and were compared between patient groups with elevated versus normal glucose values. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating sites of ischemic lesions with PSH.Of 1,281 stroke patients screened, 229 (mean age = 66.3 ± 15.9 years) met the inclusion criteria. Patients with elevated BGL were older, had higher NIHSS scores, and had larger infarcts compared to those without elevated glucose levels. Spearman rank analysis showed correlations between BGL and age, infarct size, heart rate (HR), and NIHSS scores (p <= 0.05). The VLSM analysis adjusted for these confounding factors demonstrated associations between PSH and damaged voxels in right hemispheric insular and opercular areas.The data indicate that damage in the right insulo-opercular areas contributes to PSH. The association between sympathetically mediated increase of HR and BGL suggests disinhibition of sympathetic outflow as a possible mechanism for PSH.
EVALuna2:22352

Neuroendocrine changes in patients with spontaneous supratentorial intracerebral hemorrhage - Huttner, Hagen; Kiphuth, Ines-Christine; Teuber, Linda; Lücking, Hannes; Kloska, Stephan; Staykov, Dimitre; Kuramatsu, Joji; Mauer, Christoph; Breuer, Lorenz; Dörfler, Arnd; Köhrmann, Martin (Neurocritical Care, 2013)
Background: Neuroendocrine changes have been reported after ischemic stroke, subarachnoid hemorrhage, and brain trauma. As there are no corresponding data in patients with intracerebral hemorrhage (ICH) we analyzed various neuroendocrine parameters to investigate possible alterations in hormone profiles of patients with ICH. Methods: Twenty patients with ICH were prospectively enrolled in the study. Patients were a priori parted into two groups: Ten non-ventilated patients treated on the stroke-unit (hemorrhage volumes <20 ml, "small ICH"), and 10 ventilated patients treated on the neurocritical care unit (hematoma volumes >20 ml with possible additional ventricular involvement ("large ICH"). Neuroendocrine parameters were compared between both groups referring to reference values. The following parameters were obtained over a period of 9 days in 20 patients with spontaneous supratentorial ICH: thyrotropin, free thiiodothyronine and thyroxine, human growth hormone, insulin-like growth factor 1, luteinizing hormone, follicle-stimulating hormone, testosterone, prolactin, adrenocorticotropic hormone, and cortisol. Results: Small ICH patients were in a median 71 (54-88) years old and had a mean ICH volume of 9.5 ± 6.5 ml, whereas large ICH patients were 65 (47-80) years old and showed a mean volume of 56 ± 30.2 ml. None of the patients revealed pathological alterations for thyrotropin, free thiiodothyronine, thyroxine, human growth hormone, insulin-like growth factor 1, and testosterone. There was only a mild decrease of adrenocorticotropic hormone and cortisol on day 3 in large ICH patients. Small ICH patients showed pathologically elevated levels of luteinizing and follicle-stimulating hormone throughout the observation period. Large ICH patients showed a marked increase of prolactin that developed during the course. Conclusions: Overall, neuroendocrine changes in ICH patients are not as profound as reported for ischemic stroke or subarachnoid hemorrhage. The clinical significance of increased LH and FSH levels in small ICH is unclear, whereas elevation of prolactin in large ICH was anticipated. Future randomized controlled trials should also focus on neuroendocrine parameters to clarify the impact of possible hormonal alterations on functional outcome. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hormone profile; Intracerebral hemorrhage; Neuroendocrine

No sex differences in long-term functional outcome after intracerebral hemorrhage - De Ridder, Inger; Kuramatsu, Joji; Gerner, Stefan; Madzar, Dominik; Lücking, Hannes; Kloska, Stephan; Dippel, Diederik; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2017)
Background There is conflicting evidence about the influence of sex on outcome after spontaneous intracerebral hemorrhage (sICH) and the majority of the research focused on mortality and short-term outcome only. We investigated sex differences in long-term functional outcome after sICH. Methods We used data from a prospective hospital registry and included all consecutive patients with ICH admitted to our institution between January 2006 and July 2014. Functional outcome was assessed by modified Rankin Scale evaluated 3 and 12 months after ICH. We explored the influence of sex on long-term functional outcome using multivariable regression models and additionally by means of propensity score matching. Results We analyzed 823 patients, of whom 380 (46%) women. Women were on average three years older (p < 0.001), men had more often deep hematomas (p = 0.01). Unadjusted mortality rates were significantly increased in women at three months (42% vs. 35%; odds ratio (OR): 1.35; 95% confidence interval (CI): 1.02-1.80). After adjusting for baseline prognostic factors there were no differences between men and women in short- and long-term mortality (OR = 1.01; 95% CI = 0.66-1.54 and OR = 1.04; 95%CI = 0.69-1.57, respectively) and short- and long-term unfavorable outcome (OR = 1.02; 95%CI = 0.67-1.55 and OR = 0.96; 95% CI = 0.62-1.48, respectively). Conclusion We found no sex-related differences in long-term functional outcome in patients with sICH. The apparently worse functional outcome in women can be explained by differences in age.
EVALuna2:22516

On Admission Lymphopenia in ICH Patients Is Associated with Increased Mortality and Poor Functional Outcome - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Lücking, Hannes; Kloska, Stephan; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22586

PROPHYLACTIC AND PROLONGED HYPOTHERMIA IN POOR-GRADESAH REDUCES DEGREE OF VASOSPASM AND RATE OF DELAYED CEREBRAL INFARCTIONS - Kuramatsu, J. B.; Kollmar, Rainer; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22484

Prospective intraindividual comparison of gadoterate and gadobutrol for cervical and intracranial contrast-enhanced magnetic resonance angiography - Lang, Stefan; Weibart, Marina; Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Essig, Marco; Kloska, Stephan; Dörfler, Arnd; Hölter, Philip (Neuroradiology, 2017)
PURPOSE: Gadobutrol (GB) is reported to provide improved relaxivity and concentration compared to gadoterate (GT). This study was designed to intraindividually compare quantitative and qualitative enhancement characteristics of GB to GT in cervicocranial magnetic resonance angiography (MRA) of patients with cerebrovascular disease (CVD). METHODS: Patients (n = 54) with CVD underwent two identical contrast-enhanced magnetic resonance angiography (CE-MRA) examinations of the cervical and intracranial vasculature in randomized order, using GB and GT in equimolar dose. Signal-to-noise ratios (SNR) and contrast-to-noise ratios (CNR) were obtained by two independent neuroradiologists, blinded to the applied contrast agents. Qualitative assessment was performed using a three-point scale with a focus on M1/M2 segments. RESULTS: One thousand and twenty-six vessel segments were analyzed. GB revealed a significantly higher SNR (p = 0.032) and CNR (p = 0.031) in all vessel segments. GB featured a significantly higher SNR and CNR in thoracic (p = 0.022; p = 0.016) and cervical vessels (p = 0.03; p = 0.038), as well as in the posterior circulation (p = 0.012; p = 0.005). In blinded qualitative assessment, overall preference was given to GB (p = 0.02), showing a significant better delineation of the M1/M2 segments (p = 0.041). CONCLUSION: Compared to GT, the use of GB results in a significantly higher SNR and CNR in cervical and cerebral CE-MRA, leading to a better delineation of the intracranial vasculature. Present results underline the potential of GB for improved CE-MRA assessment of vasculature in CVD patients.
EVALuna2:33134

QUANTITATIVE MAGNETIC RESONANCE IMAGING CORRELATES WITH EARLY S100B PROFILE AND FUNCTIONAL OUTCOME AFTER ACUTE BRAIN INJURY - Roeckelein, Verena; Kloska, Stephan; Uder, Michael; Buchfelder, Michael; Kleindienst, Andrea (2016)
EVALuna2:14588

Seizures among long-term survivors of conservatively treated ICH patients: incidence, risk factors, and impact on functional outcome - Madzar, Dominik; Kuramatsu, Joji; Gollwitzer, Stephanie; Lücking, Hannes; Kloska, Stephan; Hamer, Hajo; Köhrmann, Martin; Huttner, Hagen (Neurocritical Care, 2014)
Seizures are a common complication after intracerebral hemorrhage (ICH) but there is a substantial lack of information on the long-term incidence in ICH survivors and whether post-ICH seizures affect functional long-term outcome.Over a five-year period 464 consecutive patients with spontaneous ICH were analyzed. Focussing on 1-year ICH survivors, clinical, and radiological parameters were retrieved from institutional prospective databases. The occurrence of seizures was categorized as early (<=7 days) or late (>7 days). Functional outcome was assessed by mailed questionnaires and telephone interviews, and was categorized into good vs. poor (mRS: 0-2 vs. 3-5) and favorable vs. unfavorable (mRS: 0-3 vs. 4-5). Multivariate regression models were calculated to investigate risk factors associated with post-ICH seizures including an a priori defined subgroup analysis of lobar ICH patients.Among 203 long-term ICH survivors, 19.7 % developed seizures of which 55 % occurred late. Factors associated with seizures were lobar location (OR 8.10; 95 % CI 3.04-21.59; p < 0.001), sepsis (OR 4.59; 95 % CI 1.20-17.53; p = 0.026), and history of alcohol abuse (OR 3.36; 95 % CI 1.25-9.06; p = 0.017). Subgroup analysis of lobar ICH patients revealed history of alcohol abuse as the only independent predictor of post-ICH seizures (OR 5.22; 95 % CI 1.25-21.78; p = 0.024). Functional long-term outcome among survivors was slightly worse in patients with post-ICH seizures (p = 0.059). In multivariate regression modeling for prediction of poor outcome, the parameter "post-ICH seizures" again reached a statistical trend (p = 0.065), and established parameters such as age, GCS, and hemorrhage volume were independently related to poor outcome.Post-ICH seizures among long-term ICH survivors are common and may contribute to unfavorable functional outcome. Especially lobar ICH patients with a history of alcohol abuse are at risk to develop post-ICH seizures. Therefore, this subgroup may represent a target population for a prophylactic anticonvulsive treatment approach, preferably investigated in a prospective randomized trial.
EVALuna2:22307

Severity assessment in maximally treated ICH patients: The max-ICH score - Sembill, Jochen; Gerner, Stefan; Volbers, Bastian; Bobinger, Tobias; Lücking, Hannes; Kloska, Stephan; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, 2017)
As common prognostication models in intracerebral hemorrhage (ICH) are developed variably including patients with early (<24 hours) care limitations (ECL), we investigated its interaction with prognostication in maximally treated patients and sought to provide a new unbiased severity assessment tool.This observational cohort study analyzed consecutive ICH patients (n = 583) from a prospective registry over 5 years. We characterized the influence of ECL on overall outcome by propensity score matching and on conventional prognostication using receiver operating characteristic analyses. We established the max-ICH score based on independent predictors of 12-month functional outcome in maximally treated patients and compared it to existing models.Prevalence of ECL was 19.2% (n = 112/583) and all of these patients died. Yet propensity score matching displayed that 50.7% (n = 35/69) theoretically could have survived, with 18.8% (n = 13/69) possibly reaching favorable outcome (modified Rankin Scale score 0-3). Conventional prognostication seemed to be confounded by ECL, documented by a decreased predictive validity (area under the curve [AUC] 0.67, confidence interval [CI] 0.61-0.73 vs AUC 0.80, CI 0.76-0.83; p < 0.01), overestimating poor outcome (mortality by 44.8%, unfavorable outcome by 10.1%) in maximally treated patients. In these patients, the novel max-ICH score (0-10) integrates strength-adjusted predictors, i.e., NIH Stroke Scale score, age, intraventricular hemorrhage, anticoagulation, and ICH volume (lobar and nonlobar), demonstrating improved predictive accuracy for functional outcome (12 months: AUC 0.81, CI 0.77-0.85; p < 0.01). The max-ICH score may more accurately delineate potentials of aggressive care, showing favorable outcome in 45.4% (n = 214/471) and a long-term mortality rate of only 30.1% (n = 142/471).Care limitations significantly influenced the validity of common prognostication models resulting in overestimation of poor outcome. The max-ICH score demonstrated increased predictive validity with minimized confounding by care limitations, making it a useful tool for severity assessment in ICH patients.
EVALuna2:22564

Sex differences in perihemorrhagic edema evolution after spontaneous intracerebral hemorrhage - Wagner, Irina; Volbers, Bastian; Kloska, Stephan; Schwab, Stefan; Staykov, Dimitre; Dörfler, Arnd (European Journal of Neurology, 2012)
Background and purpose: Clinical data on sex differences in perihemorrhagic edema (PHE) after intracerebral hemorrhage (ICH) are lacking. Methods: Patients with spontaneous supratentorial ICH who had received standard conservative treatment were identified retrospectively. PHE development was assessed over a 14-day period on follow-up CT scans (days 1, 2-4, 5-7, 8-11, and 12-14). ICH and PHE volumes were assessed semiautomatically and compared between men and women. Results: A total of 387 patients (233 men) were included. Starting at days 2-4, women showed lower PHE values (P<0.05;/ days 2-4, 8-11) or a trend toward significance (P≤0.1; days 5-7, 12-14). Conclusions: Female sex may predict lower PHE volumes. © 2012 The Author(s) European Journal of Neurology © 2012 EFNS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Gender; Intracerebral hemorrhage; Perihemorrhagic edema

Specific Lobar Affection Reveals a Rostrocaudal Gradient in Functional Outcome in Spontaneous Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Möller, Sebastian; Huber, Angelika; Lücking, Hannes; Kloska, Stephan; Madzar, Dominik; Sembill, Jochen; Schwab, Stefan; Huttner, Hagen (Stroke, 2017)
Several studies have reported a better functional outcome in lobar intracerebral hemorrhage (ICH) compared with deep location. However, among lobar ICH, a correlation of hemorrhage site-involving the specific lobes-with functional outcome has not been established.Conservatively treated patients with supratentorial ICH, admitted to our hospital over a 5-year period (2008-2012), were retrospectively analyzed. Lobar patients were classified as isolated or overlapping ICH according to affected lobes. Demographic, clinical, and radiological characteristics were recorded and compared among lobar ICH patients using above subclassification. Functional outcome-dichotomized into favorable (modified Rankin Scale, 0-3) and unfavorable (modified Rankin Scale, 4-6)-was assessed after 3 and 12 months. Multivariate regression analysis was performed to identify predictors for favorable outcome.Of overall 553 patients, 260 had lobar ICH. In isolated lobar ICH, median hematoma-volume decreased from rostral (frontal, 22.4 mL [7.3-55.5 mL]) to caudal (occipital, 7.1 mL [5.2-16.4 mL]; P=0.045), whereas the proportion of patients with favorable outcome increased (frontal: 23/63 [36.5%] versus occipital: 10/12 [83.3%]; P=0.003). Patients with overlapping lobar ICH had larger ICH volumes than isolated lobar ICH (overlapping, 48.9 mL [22.6-78.5 mL] versus 15.3 mL [5.0-44.6 mL]; P<0.001) and poorer clinical status on admission (Glasgow Coma Scale and National Institutes of Health Stroke Scale). Correlations with anatomic aspects provided evidence of a rostrocaudal gradient with increasing gray/white-matter ratio and decreasing hematoma-volume and rate of hematoma enlargement from frontal to occipital ICH location. Multivariate analysis revealed affection of occipital lobe (odds ratio, 3.75 [1.38-10.22]) and affection of frontal lobe (odds ratio, 0.52 [0.28-0.94]) to be independent predictors for favorable outcome and unfavorable outcome, respectively.Among patients with lobar ICH radiological and outcome characteristics differed according to location. Especially affection of the frontal lobe was frequent and associated with unfavorable outcome after 3 months.
EVALuna2:22482

Teaching NeuroImages: Stroke and bilateral visual loss in a young adult: More than coincidence - Volbers, Bastian; Kaldefoss, K.; Bergua, A.; Kloska, Stephan; Schwab, Sibylle; Köhrmann, Martin (Neurology, 2012)
EVALuna2:21072

Ultra high-field SWI of the substantia nigra at 7T: reliability and consistency of the swallow-tail sign - Schmidt, Manuel; Engelhorn, Tobias; Marxreiter, Franz; Winkler, Jürgen; Lang, Stefan; Kloska, Stephan; Gölitz, Philipp; Dörfler, Arnd (BMC Neurology, 2017)
BACKGROUND: The loss of the swallow-tail sign of the substantia nigra has been proposed for diagnosis of Parkinson's disease. Aim was to evaluate, if the sign occurs consistently in healthy subjects and if it can be reliably detected with high-resolution 7T susceptibility weighted imaging (SWI). METHODS: Thirteen healthy adults received SWI at 7T. 3 neuroradiologists, who were blinded to patients' diagnosis, independently classified subjects regarding the swallow-tail sign to be present or absent. Accuracy, positive and negative predictive values (PPV and NPV) as well as inter- and intra-rater reliability and internal consistency were analyzed. RESULTS: The sign could be detected in 81% of the cases in consensus reading. Accuracy to detect the sign compared to the consensus was 100, 77 and 96% for the three readers with PPV reader 1/2/3 = 1/0.45/0.83 and NPV = 1/1/1. Inter-rater reliability was excellent (inter-class correlation coefficient = 0.844, alpha = 0.871). Intra-rater reliability was good to excellent (reader 1 R/L = 0.625/0.786; reader 2 = 0.7/0.64; reader 3 = 0.9/1). CONCLUSION: The swallow-tail sign can be reliably detected. However, our data suggest its occurrence is not consistent in healthy subjects. It may be possible that one reason is an individually variable molecular organization of nigrosome 1 so that it does not return a uniform signal in SWI.
EVALuna2:33135